2022
DOI: 10.3389/fphys.2022.969314
|View full text |Cite
|
Sign up to set email alerts
|

Antiquated ejection fraction: Basic research applications for speckle tracking echocardiography

Abstract: For years, ejection fraction has been an essentially ubiquitous measurement for assessing the cardiovascular function of animal models in research labs. Despite technological advances, it remains the top choice among research labs for reporting heart function to this day, and is often overstated in applications. This unfortunately may lead to misinterpretation of data. Clinical approaches have now surpassed research methods, allowing for deeper analysis of the tiers of cardiovascular performance (cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, current echocardiographic techniques for mice (eg, the conventional short-axis M mode) lack sensitivity to detect subtle changes in heart performance. 1 Although the modified biplane Simpson method of discs is recommended for echocardiographic assessment in humans, 2 this approach has not been utilized in mice due to challenges in obtaining on-axis apical 4-chamber views. 3 To address this limitation, we developed a novel methodology of apical 4-chamber long-axis (A4CLAX) views.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, current echocardiographic techniques for mice (eg, the conventional short-axis M mode) lack sensitivity to detect subtle changes in heart performance. 1 Although the modified biplane Simpson method of discs is recommended for echocardiographic assessment in humans, 2 this approach has not been utilized in mice due to challenges in obtaining on-axis apical 4-chamber views. 3 To address this limitation, we developed a novel methodology of apical 4-chamber long-axis (A4CLAX) views.…”
mentioning
confidence: 99%
“…To closely replicate clinical strain-imaging methodologies, we incorporated speckle tracking–based strain analysis 1,5 in the parasternal long-axis and A4CLAX views (Figure [E]). This analysis revealed that 14G-Homo LV exhibited significantly lower global longitudinal strain than WT hearts and indicated a deteriorating trend in the posterior/anterior walls at 3 months and in the septal/lateral walls at 4 months (Figure [F]).…”
mentioning
confidence: 99%